The Effect of Corrective Feedback to Improve Students’ Motivation In Speaking Skills A Perspective From EFL Learners - Mahara, Azhura Dea; Hartono, Didik (Jayapangus Press, 2024)
The effect of corrective feedback can result in various negative to positive effects on the student’s motivation in speaking skills. Corrective feedback has been used to correct the students’ mistakes. This research aims to explore the use of corrective feedback to the student’s motivation in learning speaking skills. It was conducted through an online platform for higher-level students at Brawijaya University. The respondents are 56 students who claimed to have experience in receiving corrective feedback as well as having knowledge of corrective feedback. The researcher used a Quantitative-Descriptive method by collecting data using questionaries. Using quantitative methods, this study employed close-ended questions. As a result, numerical data was expected to be analyzed for the source of the research data. The results showed that although corrective feedback can be seen as a way that can improve students’ academic skills, it is proven that it can be a negative aspect in improving students’ motivation in speaking skills. This research is expected to bring out an awareness about giving feedback to the students in order to improve their speaking skills.